Evaluación espaciotemporal del cambio global en el Departamento Sur de Haití, de 1973 al 2017 - Espinoza Cisneros, Edgar (2019)
Haiti as a country faces great environmental and societal challenges. Haiti is characterized by a high deforestation, lack of territorial planning, political and economic instability, and a growing population exerting pressure on natural resources. In this article, we analyze the historic land cover change in the Southern Department of Haiti from 1973 to 2017 and the relationship to socioeconomic and biophysical variables. All variables under change together are considered as the holistic definition of global change. We used Landsat satellite images, public data repositories and statistical correlations to analyze the directionality of the above-mentioned global change in Haiti. The results showed a marked fluctuation of crop areas, a relation of bare soil with deforested areas, as well as a decrease in forest cover after a series of hydrometeorological and sociopolitical events. In addition, we found that changes in brush area were significantly associated with the rates of change in population, temperature and the Human Development Index (HDI), while the rate of change in rainfall significantly influenced the change in crop coverage. On the other hand, changes in bare soil had a significant relationship with the rate of population change. Finally, none of the variables considered was significantly correlated with the spatiotemporal change of urban and forest coverage.